The Value of Oaks to Wildlife - Holly K. Ober (EDIS)
WEC-248, a 5-page illustrated fact sheet by Holly K. Ober, describes the value of oaks for wildlife, the food provided, differences in acorns, and other resources provided by oaks. Includes sources of additional information. Published by the UF Department of Wildlife Ecology and Conservation, August 2008.